An Analysis Of Dirty Word In Karonese Language - Christina Natalina Saragi; Usman Sidabutar; Ema Ulina Br Ginting; Carolina Pakpahan (Universitas Pahlawan Tuanku Tambusai, 2023)
This thesis entitled An Analysis of Dirty Words in Karonese at Tradisional Market Simpang Limun. The objective of the reasearch are intended to identify the types and the most dominat type of dirty words used in karonese at Tradisional Market Simpang Limun. The research was conducted by using descriptive qualitative in the analysis of the dirty words.. The researcher focused only in Karonese people who sells vegetables utterances. The source of the data were Karonese people who sells vegetables and the data from this research are dirty word karo sayings it's in the traditional market Sp. Limun to fellow Karo people. To collect data for